2022
DOI: 10.1097/pai.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

The Story of the Magee Equations: The Ultimate in Applied Immunohistochemistry

Abstract: Magee equations (MEs) are a set of multivariable models that were developed to estimate the actual Oncotype DX (ODX) recurrence score in invasive breast cancer. The equations were derived from standard histopathologic factors and semiquantitative immunohistochemical scores of routinely used biomarkers. The 3 equations use slightly different parameters but provide similar results. ME1 uses Nottingham score, tumor size, and semiquantitative results for estrogen receptor (ER), progesterone receptor, HER2, and Ki-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The incorporation of these equations into the decision-making algorithm may be cost-effective for LMICs. 35 …”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of these equations into the decision-making algorithm may be cost-effective for LMICs. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, gene expression profiling, through polymerase chain reaction (PCR) nano-string or RNA sequencing, provides an Oncotype recurrence score used for its predictive value in assessing the likelihood of disease recurrence. The Magee Decision Algorithm TM can be used to triage cases for molecular testing [49].…”
Section: Optimization Strategies For Individual-based Prognostic Fact...mentioning
confidence: 99%
“…In the TAILORx study, chemotherapy could be safely omitted in the low-risk group (RS, 0-10) of patients without axillary lymph node metastases. The intermediate-risk group (RS, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] revealed no effect of adding chemotherapy to endocrine therapy, while an RS within the range of 16-25 was associated with a prognostic benefit of chemotherapy only in patients under 50 years of age [7][8][9]. This indicated that in patients without axillary lymph node metastasis, a significant additive effect of chemotherapy existed if the RS was ≥ 26 and ≥16 in those with age > 50 years and ≦ 50 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying patients to be tested is important for reducing healthcare costs, as performing this test on patients at low clinical risk based on clinicopathological variables is not economical. Nomograms using clinicopathological variables have been reported to identify groups of patients who require chemotherapy [14][15][16]. However, these studies were conducted in Western populations and Asian women, excluding Japanese women, and data showing that these nomograms are predictive of recurrence in Japanese women are scarce.…”
Section: Introductionmentioning
confidence: 99%